Design of a High Power Amplifier for Earth-Moon-Earth Communications - Pedro Manuel Moreira Teixeira (2021)
Radio communications using the Moon reflection to overcome the Earth's curvature in longdistance communication have been in practice for more than 70 years. Since the beginning, a largesignal attenuation due to the enormous distance the signal has to travel and the low albedo of theMoon, is a great challenge to beat.Usually to make this type of communication possible a great transmission power is requiredmade possible by the use of high power RF amplifiers. Initially thousands of watts were required,but with the advances in modulation techniques and better receptions systems, the transmitterpower requirements go as low as hundreds of watts as shown in the link budget section of thisdocument, remaining however relevant problem to tackle amongst the Amateur Radio community.This thesis documents the development process of a Power amplifier capable of giving 200 Wof power at 2.4 GHz with the best efficiency possible. To fulfill this goals a revision on the stateof the art of power amplifiers was made, establishing metrics and methodologies to use during thedevelopment. Furthermore was determined that a class AB, Class F or inverse class F would be themost interesting topologies since they allow high power outputs without sacrificing the efficiencyin application where the linearity is not critical.With this is mind the workflow followed the standard development is this type of classes, usingthe circuit example present in the transistor's datasheet as a starting point. During all processAdvanced Design System 2021 software was the tool used aided by the Momentum simulationsytem, also by Keysight, allowing the generation of more realistic models of the circuits behaviour,minimizing the risk of implementation an the margin of error of the real device compared with themodel.Different bias points, bias networks and matching networks configurations were tried in orderto obtain a stable design capable of fulfilling the requirements. In the simulation of the last designthe output power wasPout=53.25dBmand with a power adder efficiency ofPAE=51.6%.Throughout the whole process a compromise mentality between efficiency, power, stabilityand linearity of the amplifier was essential, balancing the different factors into the best performingcircuit of the given application.